2000
DOI: 10.1016/s0735-1097(00)00523-4
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion syndrome: relationship of coronary blood flow reserve to left ventricular function and infarct size

Abstract: Patients with RS during primary PTCA for an anterior AMI have a transiently lower CVR than patients without RS, but sustained LV dysfunction and larger infarct size, suggesting that RS is a marker of microcirculatory reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 35 publications
1
42
0
2
Order By: Relevance
“…Our electrocardiographic findings indicated that patients with a higher WBC count on admission who underwent early recanalization had less myocardial damage before recanalization than those who underwent late recanalization, but had severe myocardial damage after recanalization. This assumption is supported by a lower QRS score, more frequent ST-segment re-elevation with a greater increase in ST-segment elevation, a marker of microcirculatory reperfusion injury, 19 and severer chest pain in the patients with early recanalization. Consequently, there were no differences between the 2 groups in myocardial damage after recanalization.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our electrocardiographic findings indicated that patients with a higher WBC count on admission who underwent early recanalization had less myocardial damage before recanalization than those who underwent late recanalization, but had severe myocardial damage after recanalization. This assumption is supported by a lower QRS score, more frequent ST-segment re-elevation with a greater increase in ST-segment elevation, a marker of microcirculatory reperfusion injury, 19 and severer chest pain in the patients with early recanalization. Consequently, there were no differences between the 2 groups in myocardial damage after recanalization.…”
Section: Discussionmentioning
confidence: 89%
“…Additional ST-segment elevation of at least 5 mm in leads V1-6 immediately after recanalization was defined as ST-segment reelevation. 10,11 In addition, the ECGs were scored according to the 32-point QRS score before and 1 h after recanalization (QRSpre, QRSpost). 12 The QRS score was additionally determined a mean of 14 days after AMI (QRSD14).…”
Section: Electrocardiographic Analysismentioning
confidence: 99%
“…2,[5][6][7] The occurrence of the noreflow phenomenon during an acute phase of MI has a negative prognostic value. Incomplete coronary reperfusion is associated with a larger infarct size, 8,9 lower left ventricular (LV) ejection fraction, 10 increased mortality, 5,11 and more frequent congestive heart failure attributable to LV remodeling. 6,9 Main causes of this phenomenon are not fully understood and involve: microvascular embolization by the aggregates composed of platelets, erythrocytes, neutrofiles, and fragments of thrombus and ruptured plaque; endothelial dysfunction; vascular smooth muscle cell (VSMC) contraction, and surrounding tissue edema.…”
mentioning
confidence: 99%
“…Additional elevation of ∑ST after reperfusion is known to be associated with reperfusion injury, which causes large infarct size and poor left ventricular function. 24 Even if the initial ∑ST is less than 10 mm, adjunctive therapy might be required in patients with a high elevation of ∑ST after reperfusion.…”
Section: Present Studymentioning
confidence: 99%